Lanthanum modified Fe-ZSM-5 zeolites for selective methane oxidation with H2O2. Issue 24 (16th November 2021) - Sun, Songmei; Barnes, Alexandra J.; Gong, Xiaoxiao; Lewis, Richard J.; Dummer, Nicholas F.; Bere, Takudzwa; Shaw, Greg; Richards, Nia; Morgan, David J.; Hutchings, Graham J.
Abstract : Lanthanum modified Fe-ZSM-5 catalyst can both increase selective methane oxidation performance and decrease H2 O2 consumption. Abstract : Selective partial oxidation of methane to methanol under ambient conditions is a great challenge in chemistry. Iron modified ZSM-5 catalysts are shown to be effective for this reaction using H2 O2 as the oxidant. However, the high consumption of H2 O2 over this catalyst presents a major disadvantage. Here we report a lanthanum modified Fe-ZSM-5 (LaFe-ZSM-5) catalyst for enhanced selective methane oxidation with suppressed H2 O2 consumption. Using 0.5 wt% LaFe-ZSM-5 pretreated with H2 the productivity of primary oxygenated products (CH3 OH, CH3 OOH, HCOOH) is 3200 mol kgLaFe −1 h −1 in 0.1 M H2 O2, with a selectivity of 98.9% to primary oxygenated products. The productivity is increased to 11 460 mol kgLaFe −1 h −1 in 0.5 M H2 O2 . Compared with Fe-ZSM-5, LaFe-ZSM-5 uses 31% less H2 O2 for obtaining per mol of product under the same conditions. In situ DRIFT spectroscopy and solid state MAS NMR revealed the high H2 O2 consumption in ZSM-5 based catalyst maybe closely related to the acidity of strong Brønsted acid sites (Si(OH)Al). The La modified ZSM-5 catalyst can decrease the acidity of the strong Brønsted acid sites and this suppresses the decomposition of H2 O2 .